2016
DOI: 10.3390/ijms17111957
|View full text |Cite
|
Sign up to set email alerts
|

Dual Function of Glucosamine in Gelatin/Hyaluronic Acid Cryogel to Modulate Scaffold Mechanical Properties and to Maintain Chondrogenic Phenotype for Cartilage Tissue Engineering

Abstract: Glucosamine (GlcN) fulfills many of the requirements as an ideal component in scaffolds used in cartilage tissue engineering. The incorporation of GlcN in a gelatin/hyaluronic acid (GH) cryogel scaffold could provide biological cues in maintaining the phenotype of chondrocytes. Nonetheless, substituting gelatin with GlcN may also decrease the crosslinking density and modulate the mechanical properties of the cryogel scaffold, which may be beneficial as physical cues for chondrocytes in the scaffold. Thus, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 62 publications
1
32
0
1
Order By: Relevance
“…The microstructure of the scaffold of cryogel samples was examined with an S-3000N scanning electron microscope (SEM) from Hitachi (Tokyo, Japan), after gold sputter coating. The porosity of the cryogel was calculated using the ethanol displacement method [68]. To study in vitro degradation of cryogel, a collagenase (30 units/mL) solution was prepared in PBS (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…The microstructure of the scaffold of cryogel samples was examined with an S-3000N scanning electron microscope (SEM) from Hitachi (Tokyo, Japan), after gold sputter coating. The porosity of the cryogel was calculated using the ethanol displacement method [68]. To study in vitro degradation of cryogel, a collagenase (30 units/mL) solution was prepared in PBS (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Gelatin is a water-soluble multipeptide polymer that is obtained by hydrolyzing collagen from animal skin and tissues. The arginine-glycine-aspartic acid (RGD) sequence of gelatin allows for better cell attachment and bioactivity [5, 17, 26, 27]. Moreover, different materials and growth factors could be fabricated additionally into cryogel scaffolds to alter physical characteristics and cellular stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The cryogel also possesses the advantage of plasticity and tailoring especially in areas like craniofacial regions which required dedicated manipulations. Previous studies demonstrated a great potential of cryogel scaffolds in tissue engineering of the bone [5, 16, 17, 25, 28], adipose tissue [6], and cartilage [26].…”
Section: Discussionmentioning
confidence: 99%
“…Доклинические испытания с использованием свиней демонстрировали биосовместимость желатиновых криогелей, их нетоксичность для организма животных. Имеются данные о добавлении к желатину других компонентов, которые повышают прочность желатиновых криогелей, например введении в исходный состав хитозана, который способствует поддержанию клеточной адгезии и пролиферации (32)(33)(34)(35).…”
Section: рис 2 микрофотографии срезов широкопористых матриц на осноunclassified